Proceedings of the Second International Afro-European Conference for Industrial Advancement AECIA 2015 - Abraham, Ajith; Wegrzyn-Wolska, Katarzyna; Hassanien, Aboul Ella; Snasel, Vaclav; Alimi, Adel M. (Advances in Intelligent Systems and Computing,, 2016)
This volume contains papers presented at the 2nd International Afro-European Conference for Industrial Advancement -- AECIA 2015. The conference aimed at bringing together the foremost experts and excellent young researchers from Africa, Europe and the rest of the world to disseminate the latest results from various fields of engineering, information, and communication technologies. The topics, discussed at the conference, covered a broad range of domains spanning from ICT and engineering to prediction, modeling, and analysis of complex systems. The 2015 edition of AECIA featured a distinguished special track on prediction, modeling and analysis of complex systems -- Nostradamus, and special sessions on Advances in Image Processing and Colorization and Data Processing, Protocols, and Applications in Wireless Sensor Networks.